Personal Financial Planning for Luang Prabang Provincial People's Council Staff - manichith, keola (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study aimed to examine the personal financial planning behaviors of employees of the Luang Prabang Provincial People's Council, and to explore their opinions on the importance of personal financial planning. This research employed a survey method targeting 43 employees of the Luang Prabang Provincial People's Council. Data were collected using a questionnaire and analyzed to determine the relevant values. The results show that personal financial planning behaviors among employees are generally at a moderate to high level. In detail, the majority engage in self-planning (93.9%), followed by depositing with a bank or financial institution (36.4%). The purposes for planning include retirement (42.4%), risk management (57.6%), and consumption such as purchasing cars or household appliances (45.5%). Additionally, 33.3% have savings plans, 66.7% are willing to accept some level of risk, and 36.4% expect a return of 5–10% per year. About 51.1% plan for a financial horizon of 3–6 years, and 27.3% aim to accumulate between 700,001–1,000,000 kip per month. The majority emphasize financial stability (81.8%), diversify risk by depositing in various financial institutions (39.4%), and manage risk primarily by thoroughly studying information before investing (75.8%). Regarding their opinions on the importance of external factors in personal financial planning, most employees rated these as highly important, with an average score of 3.72 and a standard deviation of 0.94. A detailed analysis ranked the importance of these factors as follows: the economy (mean = 4.08, SD = 1.04), society (mean = 3.78, SD = 0.90), technology (mean = 3.60, SD = 0.91), and politics (mean = 3.42, SD = 0.94).